2015
DOI: 10.1186/1472-6947-15-s3-s6
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study for development of a novel tool for clinical decision making to identify fallers among ophthalmic patients

Abstract: BackgroundFalls in the elderly is a major problem. Although falls have a multifactorial etiology, a commonly cited cause of falls in older people is poor vision. This study proposes a method to discriminate fallers and non-fallers among ophthalmic patients, based on data-mining algorithms applied to health and socio-demographic information.MethodsA group of 150 subjects aged 55 years and older, recruited at the Eye Clinic of the Second University of Naples, underwent a baseline ophthalmic examination and a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Table 3 showed the comparison of the performances of the proposed algorithm for fall risk assessment and several functional tests for fall prediction, confirming that the system achieved satisfactory performances. The system will be also integrated with a novel method to identify ophthalmological patients at higher risk of falls, which was described elsewhere [42]. Moreover, the system appeared to be well accepted by almost all the patients (95 %) with a limited amount of data lost (<20 %), thus showing that the electrocardiographic data could be reliably acquired by the developed system.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Table 3 showed the comparison of the performances of the proposed algorithm for fall risk assessment and several functional tests for fall prediction, confirming that the system achieved satisfactory performances. The system will be also integrated with a novel method to identify ophthalmological patients at higher risk of falls, which was described elsewhere [42]. Moreover, the system appeared to be well accepted by almost all the patients (95 %) with a limited amount of data lost (<20 %), thus showing that the electrocardiographic data could be reliably acquired by the developed system.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Two hundred subjects were enrolled into the first part of the study, which was to identify retrospective fallers and which was reported previously [20]. Those 200 subjects were invited to complete a follow-up prospective study, which is the currently reported study.…”
Section: Methodsmentioning
confidence: 99%
“…Socio-demographic and medical data were recorded with a standardized questionnaire that was developed ad hoc and validated on retrospective data as detailed in our previous study [20]. Briefly, we selected variables, which have been investigated as potential risk factors for falls in previous studies, including but not limited to those on visual impaired subjects [4, 11, 16, 2431].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations